Hospital characteristics preferred by medical students for their residency programs: A nationwide matching data analysis. (26th August 2020) - Nishizaki, Yuji; Ueda, Rieko; Shinozaki, Tomohiro; Tokuda, Yasuharu
Abstract: Background: In 2004, Japan introduced a mandatory 2‐year postgraduate training program for graduating medical students with a super‐rotation curriculum. A national matching system was established to determine the hospital residency programs best suited for the students. We examined the hospital characteristics preferred by applicants for residencies. Methods: A nationwide cross‐sectional study was conducted. Data on salaries, bonuses, and number of accepted ambulances were compiled from the Residency Electronic Information System. Information on the prefectural population, urban area, and number of senior residents (postgraduate years 3–5) for specialty training was extracted from data published on the web page. The ratio of the number of first‐choice applicants to recruitment capacity (matching ratio) for each program was compared between the characteristics of the hospitals and prefectures. Results: A strong linear relationship was observed between the number of first‐choice applications and the allocated number of resident positions (correlation coefficient, .72). The matching ratio was greater in community hospitals (2.10 times compared with university hospitals; 95% confidence interval [CI], 1.75–2.53), in hospitals with higher numbers of accepted ambulance cases (1.05 times per 1000 annually; 95% CI, 1.03–1.08), and in hospitals that served a larger prefectural population (1.05 times per million; 95% CI, 1.02–1.08). Conclusions: Financial incentives do not seem to attract residency applicants. Applicants prefer non‐university hospitals located in populous areas and those that accept larger number of ambulance cases. To recruit junior residents, an emergency department may need to have higher activity with larger numbers and variety of cases. Abstract : Financial incentives do not seem to attract residency applicants. Applicants prefer non‐university hospitals located in populous areas and those that accept larger numbers of ambulance cases. To recruit junior residents, an emergency department may need to have higher activity with larger numbers and variety of cases.